Interdit et interdiction. Quelques variations textuelles et variantes sémantiques - Geneviève Koubi (Droit et Cultures, 2009)
Interdict and prohibition are two terms frequently used in the legal vocabulary. They do not express the same idea and have to be read in a different manner. They are not synonymous. Their respective use in legal texts varies according to various parameters (territory, time, field, perspective, etc.). But both terms tend to format behaviour, posture, attitude or to limit a power, a force, an activity and aim at determining responsibility or sanction when transgression is registered.